Caractérisation des matorrals et des garrigues à Urginea pancration Phil. dans le Djebel Tessala (Algérie occidentale) - Mohamed Ali Bouzidi; Ali Latrèche; Ilhem Attaoui; Zoheir Mehdadi; Mohamed Benyahia (Physio-Géo)
A characterization of habitats currently occupied by Urginea pancration (Steinh.) Phil. in Tessala Mounts between 700 and 1000 m of altitude is presented. Twelve plots were studied according to 14 ecological parameters of which slope, exposure, altitude, soil type…This study permitted to define the biological and edaphic habitat of this plant and to show the floristic richness of the sites which it occupies in Tessala Mounts. The obtained results show that it takes up a place more important in the matorral and scrubland when soil conditions are harsh and that the degradation of vegetation cover is important.